Pendampingan penyusunan RPP K-13 bagi guru MI yang belum bersertifikasi di Kabupaten Sukoharjo, Boyolali dan Karanganyar Tahun 2021 - Pratiwi Rahmah Hakim; Kustiarini; Saiful Islam; Silva Intan Fajar Saputri (LPPM Universitas Lampung, 2022)
The service activities carried out by the team from FIT UIN Raden Mas Said Surakarta aim to: 1) provide facilities for MI teachers who have not been certified in preparing the 2013 Curriculum Implementation Plan and the Independent Curriculum; 2) Providing consultation assistance in the preparation of the 2013 learning implementation plan and the Independent Curriculum; 3) Help provide contextual solutions in solving problems related to the preparation of the 2013 Curriculum learning implementation plan and the Independent Curriculum; 4) Building a school quality culture through the making of RPP by teachers in a creative, innovative, contextual and sustainable manner. This activity was carried out in Sukoharjo Regency, Boyolali Regency, and Karanganyar Regency. The implementation of the activities will be carried out from September 1-18, 2021. The result of this mentoring activity is the preparation of learning implementation plan instrument. Regarding the implementation of devotion community, there are obstacles experienced by teachers in the preparation of learning implementation plan and online learning implementation plan, including: 1) Participants need a long time in determining the material to be compiled into learning implementation plan; 2) Discussions between members in groups are less communicative: 3) Participants still have difficulty in making learning indicators; 4) Difficulty in determining online learning media; 5) Teachers have difficulty in developing learning objectives based on ABCD (Audience, Behavior, Condition, Degree); 6) Teachers have difficulty in making authentic assessments; 7) The teacher has difficulty in determining which materials will be included in the online lesson plans because the online learning time is shorter than face-to-face learning; 8) There are some participants who are of advanced age so they are less motivated in making lesson plans; 9) During the practice of making media, it appears that some participants are still confused about using the Kine master application, for example in recording videos; 10) There are some participants who do not bring the syllabus which will be used as a reference for making learning implementation plan.